2004
DOI: 10.1080/00986440490464264
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of Oxide Nanoparticles Prepared by Induction Thermal Plasmas

Abstract: The reactive evaporation method of injected metal powders was investigated for preparing oxide nanoparticles. The method has advantages such as evaporation is enhancement of the injected powder owing to exothermic reaction heat of the metal powder oxidation in induction thermal plasmas. Tangential gas flow injection to the plasma tail flame controls the diameter and the yield of the oxide nanoparticles. The purpose of this research is to investigate the effect of the injection gas flow on the preparation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…discussed the pressure effect on particle size and concluded that higher pressure induces larger particle size due to the higher residence time and lower cooling rate, while lower pressure causes a smaller size. Unlike previous research [56], the radial quenching Ar gas in this research had no significant influence on the particle size, which was attributed to the turbulent flow caused by the quenching gas. When the quenching gas was changed to He, which is lighter than Ar and thus cannot cause turbulence, the mean particle size decreased from 12 to 8 nm.…”
Section: Development Of Rf-icp Spraying Engineeringcontrasting
confidence: 81%
See 1 more Smart Citation
“…discussed the pressure effect on particle size and concluded that higher pressure induces larger particle size due to the higher residence time and lower cooling rate, while lower pressure causes a smaller size. Unlike previous research [56], the radial quenching Ar gas in this research had no significant influence on the particle size, which was attributed to the turbulent flow caused by the quenching gas. When the quenching gas was changed to He, which is lighter than Ar and thus cannot cause turbulence, the mean particle size decreased from 12 to 8 nm.…”
Section: Development Of Rf-icp Spraying Engineeringcontrasting
confidence: 81%
“…To further improve the nanopartic1es's yield, size distribution, and shape, tangential injection of cooling gas can be applied combined with combustion-aided SPS. Employment of tangentially injected cooling gas has proved to be an efficient way to increase the quenching rate, thereby controlling the nanopartic1es' yield and size [93,132]. According to Swihart [125], a proper quenching rate may produce spherical nanopartic1es if the coalescence process is faster than coagulation.…”
Section: Future Workmentioning
confidence: 99%
“…Induction thermal plasma (ITP) has become very popular in material processing due to several of its inherent characteristics: such as contamination free (no electrode), high thermal gradient (between torch and reaction chamber), wide pressure range and high enthalpy. ITP have extensively been used for the synthesis and surface treatment of fine powders since couple of decades as a clean reactive heat source [Fan, 1997], [Watanabe, 2004]. ITP technology may ensure essentially the in-flight one-step melting, short melting time, and less pollution compared with the traditional technologies that have been using in the glass industries for the vitrification of granulated powders.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many researchers [3][4][5][6][7] have become involved in the investigation of the tailoring of produced nano-powders with specific properties, such as their degree of agglomeration and size distribution. Furthermore, for some applications and the associated process control and for modeling calibration, there is the need to access to the formation and growth history during the induction plasma synthesis process.…”
Section: Introductionmentioning
confidence: 99%